How HSCs Colonize and Expand in the Fetal Niche of the Vertebrate Embryo: An Evolutionary Perspective - Mahony, Christopher B.; Bertrand, Julien Y. (Frontiers in Cell and Developmental Biology, 2019)
Rare hematopoietic stem cells (HSCs) can self-renew, establish the entire blood system and represent the basis of regenerative medicine applied to hematological disorders. Clinical use of HSCs is however limited by their inefficient expansion ex vivo, creating a need to further understand HSC expansion in vivo. After embryonic HSCs are born from the hemogenic endothelium, they migrate to the embryonic/fetal niche, where the future adult hematopoietic stem cell (HSC) pool is established by considerable expansion. This takes place at different anatomical sites and is controlled by numerous signals. HSCs then migrate to their adult niche, where they are maintained throughout adulthood. Exactly how HSC expansion is controlled during embryogenesis remains to be characterized and is an important step to improve the therapeutic use of HSCs. We will review the current knowledge of HSC expansion in the different fetal niches across several model organisms and highlight possible clinical applications.